Determining the buyer-supplier relationships in international market: evidence of Indonesian products - Ervyna Rizki Febrianny; Mustika Sufiati Purwanegara (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2019)
This paper examines how trust and commitment impact repurchase intention and relationship performance in international market from overseas buyers to Indonesian suppliers. To achieve this objective, data were collected through a survey using a structured questionnaire to overseas buyers who have been engaging with Indonesian suppliers. A total respondent of 84 were collected. A confirmatory factor analysis was measured in this study to test the reliability and validity of the measurement model. The Partial Least Square technique also was used to test the conceptual framework of this study. The result shows that trust is significantly influenced commitment in the International buyer-supplier relationship. Commitment also significantly influenced repurchase intention and relationship performance of overseas buyers in buying Indonesian products.